2018
DOI: 10.1071/hc18006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the structure and processes of primary health care for young indigenous children

Abstract: INTRODUCTION Primary health care organisations need to continuously reform to more effectively address current health challenges, particularly for vulnerable populations. There is growing evidence that optimal health service structures are essential for producing positive outcomes. AIM To determine if there is an association between process of care indicators (PoCIs) for important young indigenous child health and social issues and: (i) primary health-care service and child characteristics; and (ii) organisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…We are also focusing on ‘structures of care’ such as education and training, capacity building and improvements in the organisation of health systems. [14, 48]…”
Section: Discussionmentioning
confidence: 99%
“…We are also focusing on ‘structures of care’ such as education and training, capacity building and improvements in the organisation of health systems. [14, 48]…”
Section: Discussionmentioning
confidence: 99%
“…26,31,65,[69][70][71] Furthermore, a study published in 2018 utilising child health audit data from 1,554 Aboriginal children in primary health services also found that leadership styles, defining roles and responsibilities and capacity building combined with alignment to guidelines improved anaemia treatment. 72 A range of policy, systemic and organisational factors also con- improve practice support implementation 48 as was found with the Barunga Program. CQI was the main monitoring approach used in the Program, which has been shown to be culturally acceptable and has resulted in positive outcomes in other Aboriginal communities.…”
Section: Evaluation Of the Program Through An Implementation Lensmentioning
confidence: 94%
“…CQI was the main monitoring approach used in the Program, which has been shown to be culturally acceptable and has resulted in positive outcomes in other Aboriginal communities. 72,73 When staff capacity was limited, a task-orientated approach dominated, prioritising Iron Run clinical tasks. A more holistic approach, however, was favoured when the Program team was wellresourced, allowing for more counselling and health promotion by the Health Centre, and through external partnerships with other organisations working to support community development and well-being.…”
Section: Evaluation Of the Program Through An Implementation Lensmentioning
confidence: 99%
“…anaemia and child neurodevelopment if they had received an Indigenous-specific health assessment than those children who received acute care (2466 client records of children aged 3-59 months, from 109 Indigenous PHC centres, 2012-14) (Strobel et al 2018). These findings are consistent with other Australian research that has found Indigenous-specific health assessments to be useful for identifying new health issues, including chronic disease risk factors for individuals and for service populations (Miller et al 2002;Spurling et al 2009;Coleman et al 2011;Bailie et al 2013;Dutton et al 2016).…”
Section: What Does This Paper Add?mentioning
confidence: 99%